2009
DOI: 10.18632/aging.100099
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila melanogaster p53 has developmental stage-specific and sex-specific effects on adult life span indicative of sexual antagonistic pleiotropy

Abstract: Truncated and mutant forms ofp53 affect life span in Drosophila, nematodes and mice, however the role of wild-type p53 in aging remains unclear. Here conditional over-expression of both wild-type and mutant p53 transgenes indicated that, in adult flies, p53 limits life span in females but favors life span in males. In contrast, during larval development, moderate over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 53 publications
6
58
1
3
Order By: Relevance
“…The p53B isoform may also participate in other processes that Drosophila p53 has been implicated in, which include the culling of primordial germ cells, meiotic checkpoints, DNA repair, stem cell divisions, and tissue regeneration. 41,[60][61][62][63][64][65][66][67][68][69] Our results indicate that p53A and p53B localize to nuclear bodies and physically associate, an interaction that is likely direct through the conserved p53 oligomerization domain. Therefore, p53 tetramers may be heterogeneous and have different ratios of p53A and p53B subunits.…”
Section: Discussionmentioning
confidence: 64%
“…The p53B isoform may also participate in other processes that Drosophila p53 has been implicated in, which include the culling of primordial germ cells, meiotic checkpoints, DNA repair, stem cell divisions, and tissue regeneration. 41,[60][61][62][63][64][65][66][67][68][69] Our results indicate that p53A and p53B localize to nuclear bodies and physically associate, an interaction that is likely direct through the conserved p53 oligomerization domain. Therefore, p53 tetramers may be heterogeneous and have different ratios of p53A and p53B subunits.…”
Section: Discussionmentioning
confidence: 64%
“…P53 has been linked with aging in mammalian system. Like its mammalian counterpart, Drosophila P53 (dP53) plays a pivotal role in mediating DNA damage‐induced apoptosis and has been found to be involved in regulating aging (Waskar et al ., 2009). Our testing indicated that there was an increase in dP53 expression in older animals.…”
Section: Resultsmentioning
confidence: 99%
“…This was most clearly demonstrated by the study by Waskar et al 20 showing that p53 influences life span in flies in p53 dose-specific, fly tissue-specific, developmental stage-specific, and sexspecific manners. Furthermore, the type and extent of stress that activates p53 could also be a factor to determine Figure 3.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 90%
“…Furthermore, although overexpression of wild-type p53 at a high level in the larval stage was toxic to larval development, overexpression of p53 at a moderate level extended life span in both males and females. 20 Thus, the regulation of life span by p53 in flies is context dependent; it appears to be not only p53 dose specific but also fly tissue, sex, and developmental stage specific. …”
Section: P53 and Longevity In Drosophilamentioning
confidence: 99%
See 1 more Smart Citation